1984
DOI: 10.1093/oxfordjournals.jbchem.a134720
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosidediphosphate Kinase from Ehrlich Ascites Tumor Cells1

Abstract: A phosphate-incorporating protein has been highly purified from the cytosol of Ehrlich ascites tumor cells (EAT cells). The nitrocellulose membrane method was used to follow the progress of the purification by quantitation of the [32P]phosphorylated form of the protein. The purified protein was identified as an NDP-kinase since it exhibited NDP-kinase activity and had enzyme characteristics in common with other NDP-kinases from various mammalian cells. The purified NDP-kinase was found to have a molecular weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

1986
1986
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…The enzyme reaction was initiated by the addition of 20pM [y-32P]ATP (3000 cpm/pmol) and incubated for 5 min in an ice bath. The [32P]phosphate incorporation into the fractions was determined by the nitrocellulose membrane method as described in [2-51 290 DEAE-cellulose column chromatography showed the existence of two distinct NDP kinases (F-I, F-II), composed of two similar distinct subunits ( fig.3), in mammalian cells such as mouse NK [2,3], EAT [5] and HeLa S3 cells [4,6]. Although it would seem that the existence of two distinct NDP kinases is common in mammalian cells, there are some dissimilarities between these two enzymes: (i) these two enzyme subunits are differentially phosphorylated when incubated with [Y-~~P]ATP in the presence of divalent cations (Ca2+ and Mg2+) (fig.2); (ii) the [32P]phosphate incorporating (phosphoenzyme-forming) activity of the F-I enzyme is relatively stable as compared with that of the F-II enzyme after incubation for 20 min at 60°C [6]; and (iii) the biochemical properties of the enzyme-associated GTP-binding protein are clearly different in each enzyme [6].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The enzyme reaction was initiated by the addition of 20pM [y-32P]ATP (3000 cpm/pmol) and incubated for 5 min in an ice bath. The [32P]phosphate incorporation into the fractions was determined by the nitrocellulose membrane method as described in [2-51 290 DEAE-cellulose column chromatography showed the existence of two distinct NDP kinases (F-I, F-II), composed of two similar distinct subunits ( fig.3), in mammalian cells such as mouse NK [2,3], EAT [5] and HeLa S3 cells [4,6]. Although it would seem that the existence of two distinct NDP kinases is common in mammalian cells, there are some dissimilarities between these two enzymes: (i) these two enzyme subunits are differentially phosphorylated when incubated with [Y-~~P]ATP in the presence of divalent cations (Ca2+ and Mg2+) (fig.2); (ii) the [32P]phosphate incorporating (phosphoenzyme-forming) activity of the F-I enzyme is relatively stable as compared with that of the F-II enzyme after incubation for 20 min at 60°C [6]; and (iii) the biochemical properties of the enzyme-associated GTP-binding protein are clearly different in each enzyme [6].…”
Section: Resultsmentioning
confidence: 99%
“…Using this method, we purified NDP kinases to a high degree from various mammalian cells, such as mouse NK [3], Ehrlich ascites tumor [5] and HeLa S3 cells [4,6]. We found that the purified enzymes from different mammalian cells consist of two distinct subunits [a-subunit (Mr 20000-22000) and P-subunit (Mr l&X000-19000)] [2-61.…”
Section: Abbreviationsmentioning
confidence: 99%
“…Although NDPK has been measured in a wide range of organisms from bacteria to higher plants to mammalian cells (Parks and Agarwal 1973), we are aware of only one report of a measurement in a unicellular autotroph (Klein and Follmann 1988) and no cases of measurements in marine phytoplankton. There has been speculation about the importance of NDPK in cell growth processes during development (Dickinson and Davies 197 l), including a correlation with growth rate in mammalian tumor cells (Koyama et al 1984) and evidence of relationships between NDPK and growth rate in crustaceans (Berges 1989, Berges et al 1990). In multicellular organisms, however, the relationship between NDPK and growth is complicated by changes in body size and composition during development.…”
mentioning
confidence: 99%
“…Μη φυτικές NDP κινάσες Η NDP κινάση έχει καθαριστεί μέχρι ομογένειας από διάφορες πηγές (Richard et al, 1975;Agarwal and Parks, 1971;Koyama et al, 1984;Kimura and Shimada, 1988). Στη δεκαετία του 60 και αρχές του 70 υπήρξε ένα ενθουσιώδες κύμα μελετών αλλά μόνον πολύ αργότερα άρχισε να εμφανίζεται μια πιο καθαρή εικόνα του ενζύμου.…”
Section: ιδιοτητες των Ndp κινασωνunclassified